Profiling Basic English Proficiency Among Mechanical Engineering Students: Pedagogical Implications for EFL Classrooms - Agnes Arum Budiana; Pretti Ristra; Alfansuri (Lembaga Teewan Journal Solutions, 2026)
English proficiency is a crucial competence for vocational higher education students, particularly in engineering fields where access to technical information and global communication increasingly relies on English. However, many first-semester students enter polytechnic institutions with limited basic English skills. This study aimed to describe the basic English proficiency of first-semester Mechanical Engineering students at Politeknik Negeri Bengkalis. A descriptive quantitative research design was employed, involving 131 students from five classes selected through total sampling. Data were collected using a basic English proficiency test focusing on fundamental grammar, simple sentence construction, and general vocabulary. The data were analyzed using descriptive statistics, including mean scores, score distribution, and proficiency levels.The findings revealed that students’ overall English proficiency was low to moderate, with a mean score of 60.57. More than half of the participants were classified into very low and low proficiency categories, indicating insufficient mastery of foundational English skills. The results also showed considerable variation in students’ performance, reflecting diverse educational backgrounds and unequal English exposure prior to entering higher education.